The Self in the Role of Another:The Quest for Identity in Girish Karnad’s Hayavadana and Naga-Mandala - C. Samuel (ILN Journal: Indian Literary Narratives, 2024)
The relative roles of colonisers and colonised can be explored in postcolonial literature, along with resistance and disagreement against hegemonic empires. It can also talk about how colonialism shaped cultural prejudices and how language has given rise to inferior identities. Topics including racial identity, gender, place, migration, obstruction, and enslavement are common in postcolonial discourse. Famous and outstanding literary works that portray the identity crisis and imperfection are Hayavadana and Naga-Mandala by Girish Karnad. All along their lives, humans chase for the ideal of completeness. However, they fail to remember that completeness is an unreachable goal. Intense identity and imperfection crises are the subject of this article. It also shows how much more powerful the mind is than the body. Karnad paints an authentic image of his characters as they struggle within to maintain an identity and achieve the unattainable ideal of completeness. The theme “incompleteness and identity crisis” immediately generates a desire to choose Girish Karnad’s plays, which incorporate incompleteness of diverse personalities depicted with distinct circumstances and cultures, thus indicating various elements of identity crisis. This article attempts to analyse the ideology of identity crisis which is an entity of postcolonialism citing select plays of Girish Karnad namely, Hayavadana and Naga-Mandala.